Effect of Parboiling Conditions on Physical and Cooking Quality of Selected Rice Varieties. (9th September 2020) - Meresa, Ayenew; Demissew, Ayalew; Yilma, Seifu; Tegegne, Getu; Temesgen, Kiber
Abstract : Most locally cultivated rice varieties in Ethiopia have low physical (low head rice yield, high broken rice yield, and high percentage of chalkiness) and cooking qualities (low water uptake ratio and swelling ratio). Parboiling, a process which involves soaking, steaming, and drying, has been identified as a key technique to improve cooking and milling quality of rice. The current study is aimed at elucidating the effect of parboiling on physical and cooking qualities of three rice varieties (Gumara, Edget, and Narica4) collected from Fogera National Rice Research and Training Center, Amhara region, Ethiopia. Each rice variety was subjected to different soaking temperatures (40°C, 50°C, 60°C, 70°C, and 80°C) and steaming time (10, 20, 30, 40, and 50 minutes). The treatment effect results indicated that parboiling has a significant effect (P < 0.05 ) on head rice yield and percentage of broken rice with increased soaking temperature and steaming time as compared to the control. For instance, percent head rice yield increased as soaking temperature (from 40 to 80°C) and steaming time (from 10 to 50 min) increased: for Gumara, from 4.07 to 93.6%, for Edget, 9.47 to 96.53, and from 3.20 to 91.67 for Narica4. Percentage chalkiness had decreased as soaking temperature and steaming time increased: 97.33% to 0.00% for Gumara, 97.80% to 0.00% for Edget, and 100.00% to 0.13% for Narica4 as compared to 100% for control of all varieties. The minimum cooking time was identified as 16-23 min for Gumara, 16-23 min for Edget, and 15-20 min for Narica4 rice varieties. The result of the present study clearly showed that parboiling with high soaking temperature and steaming time increased the head rice yield, water uptake ratio, decreased percentage chalkiness, and enhanced the overall quality of the rice varieties.